ANALISIS FRAUD DIAMOND DALAM MENDETEKSI FRAUDULENT FINANCIAL STATEMENT - Wuri Kusumarini, - (2019)
This study aimed to analyze the factors that encourage fraudulent financial reports with analysis of diamond fraud. This research analyzes the influence of variable pressure proxied by external pressure, the opportunity proxied by ineffective monitoring, razionalization proxied by change in auditor, and the capability to replace director proxies against financial statements fraudulent. The sample was a total of 33 mining companies are listed on the Indonesian Stock Exchange in the period 2015-2017. This paper uses logistic regression with some help of programming data using SPSS (Statistical Product and Service Solution) 25th. The results show that external pressure, inneffective monitoring, change in auditor proved to be significantly negative and replaced of director proved to be significantly positive. The results of this study are expected to be a reference for further researchers and users of other financial information in detecting fraud on the financial statements.